Isotopic range of bioavailable strontium on the Peloponnese peninsula, Greece: A multi-proxy approach - Frank, Anja B.; Frei, Robert; Triantaphyllou, Maria; Vassilakis, Emmanuel; Kristiansen, Kristian; Frei, Karin M. (Science of The Total Environment, 2021)
Sr isotopes are a powerful tool used for provenancing in many disciplines, but their successful application requires the availability of robust Sr baselines of potential target areas. This study presents 87Sr/86Sr signatures and Sr concentrations of water, plants and soil leachates from the Peloponnese peninsula, Greece, to establish the first comprehensive bioavailable Sr isotope baseline for this region. Additionally, this study aims to evaluate which proxy is most suitable to characterise bioavailable Sr in a geologically complex area also exposed to foreign aeolian Sr sources. Our recorded bioavailable Sr isotope signatures correspond well with the surface lithologies characteristic of the Peloponnese. Unradiogenic 87Sr/86Sr ratios and a narrow isotope range (0.70779 - 0.70955) characterise the bioavailable Sr signatures of the sedimentary deposits and more radiogenic and isotopically variable values (0.70791 - 0.72370) were measured for metamorphic and igneous rock outcrops. The differences in 87Sr/86Sr values measured between proxies of one site are comparatively low for samples from the sedimentary and igneous deposits, while the overall spread in 87Sr/86Sr values is wider for samples from metamorphic deposits. We propose to define bioavailable 87Sr/86Sr baseline ranges as the average bioavailable 87Sr/86Sr ratio of all proxies of each lithology ± its double standard deviation (x̅ ± 2σ). This results in narrow baselines for the sedimentary outcrops of 0.70832 ± 0.00053 (n=58) for clastic sediments and 0.70835 ± 0.00089 (n=29) for chemical sediments. The metamorphic deposits are characterised by wider bioavailable 87Sr/86Sr baselines of 0.70906 ± 0.00116 (n=4) and 0.71429 ± 0.01133 (n=13) for marble and schist, respectively. The bioavailable Sr baseline for igneous rock outcrops is also characterised by a comparatively wide range with 0.70950 ± 0.00259 (n=7). The wide range in inter- and intra-site specific bioavailable 87Sr/86Sr variation observed in this study emphasise the need for comprehensive multi-proxy sampling strategies within geologically-complex areas.
Keywords: Multi-proxy comparison; Provenancing; Sr/Sr baseline; Strontium isotopes